ANALISIS PENERAPAN ACTIVITY BASE COSTING SEBAGAI PENENTUAN TARIF JASA RAWAT INAP PADA RSUD NGIMBANG LAMONGAN TAHUN 2018 - Mila Defi Anjani; Indah Kurniyawati (Jurnal Riset Akuntansi, 2019)
The hospital earns income from inpatient services, which rates for inpatient services still use traditional cost methods that only use one scost driver, namely the number of hospitalization days. So it is necessary to apply the activity based costing method. This study uses a qualitative method. The results of the study concluded that the tariff calculation for inpatient services using the activity based costing method was different, namely for the activity based costing method VVIP and VIP gave smaller results, while the Class I, Class II and Class III calculations used the activity based costing method to produce greater than the rate determined by the hospital. With the difference for VVIP Class Rp.238,347.76, VIP Class Rp.56,947.5, Class I Rp.119,078.2, Class II Rp.237,764.1, Class III Rp.294,018.